Preliminary Detection Method for Heavy Metal Biomonitoring via Inhibitive Assay of Brain Acetylcholinesterase from Diodon hystrix - Noreen Nordin; Rahmath Abdulla; Rohana Tahir; Roslina Jawan; Diana Demiyah Mohd Hamdan; Nur Zaida Zahari; Jualang Azlan Gansau; Mohd Yunus Shukor; Mohd Khalizan Sabullah (UNIVERSITI MALAYSIA TERENGGANU, 2021)
Acetylcholinesterase (AChE) is a well-known enzyme sensitive to pesticide exposure, but heavy metal sensitivity is rarely reported. Here, AChE extracted from the brain tissue of Diodon hystrix was exploited and used in a fast and economical way to sensitively detect the existence of heavy metals in a water sample. An inhibitive enzyme assay was conducted, and the activity of AChE is found to be sensitive (> 20% inhibition) to sub-million levels of arsenic, cadmium, nickel, and zinc, and less sensitive (< 20% inhibition) to copper and lead. While exposure to argentum, cobalt, and chromium show no significant inhibition; AChE is not sensitive to those metal ions (p < 0.05). Field test work has proved that the assay is suitable for preliminary detection of heavy metal contamination in the river, especially near industrial and mining sites. Secondary validation was performed using ICP-OES to identify and measure the number of elements in the sample and compare them to the inhibition level of AChE activity